Daptomycin-Nonsusceptible, Vancomycin-Intermediate, Methicillin-Resistant Staphylococcus aureus Endocarditis. Issue 2 (2012) - Yu, Ryan; Dale, Suzanne E; Yamamura, Deborah; Stankus, Vida; Lee, Christine
Abstract : Due to the emergence of Staphylococcus aureus with reduced vancomycin susceptibility, newer antibiotics, including daptomycin, have been used to treat methicillin-resistant S aureus infections. Daptomycin is a cyclic lipopeptide that is approved to treat S aureus bacteremia and right-sided endocarditis, and reports of S aureus with reduced susceptibility to daptomycin are infrequent. To our knowledge, the present report describes the first Canadian case of daptomycin-nonsusceptible, vancomycin-intermediate S aureus infection.